Political Conditions and Doctrinal Foundations of the Transformation in Poland in Comparison with Other Post-Communist Countries (Economic and Political Thought, 2010)
The article presents a diagnostic assessment of the political and economicsystem transformation process in Poland. The author expresses an opinionthat Solidarity as a mass social and political organization played a significantrole only in the destruction of communism but not in the creation of a newpolitical system. Its main leader, Lech Walesa, did not allow it to do so. And itwas substituted in that role by the conservative – formerly communist – powerafter it had eliminated the orthodox communists’ fraction. In co-operationwith the Democratic Union and later the Union of Freedom, and Lech Walesahimself, it substantially contributed to the creation of a new post-communistsystem. In such conditions the economic system could not be formed followingthe model of fair capitalism but political capitalism based on the principlesof pseudo-liberal ideology and propaganda and a contemptuous treatment ofthe academic science of liberal-market economics. The article also presentstwo forecast scenarios of future changes of the political system.